PERAN DIGITAL MARKETING DALAM MENDUKUNG RESILIENSI BISNIS UMKM DI TENGAH VOLATILITAS NILAI TUKAR RUPIAH: KAJIAN LITERATUR - Pefriyadi Pefriyadi (Creative Research Management Journal, 2026)
This study examines the role of digital marketing in supporting the business resilience of Micro, Small, and Medium Enterprises (MSMEs) amid rupiah exchange rate volatility. It employs a Systematic Literature Review (SLR) based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. Literature was collected from the Scopus, Google Scholar, and Garuda databases, covering publications from 2020–2025. The search identified 186 articles, which were systematically screened through duplicate removal, title and abstract screening, eligibility assessment, and quality appraisal, resulting in 38 articles for the final synthesis. Data were analyzed using data extraction, thematic categorization, and narrative synthesis to identify patterns and conceptual relationships across previous studies. The findings indicate that digital marketing supports MSME business resilience by expanding market access, improving promotional efficiency, strengthening customer relationships, diversifying marketing channels, and enhancing adaptability to economic uncertainty. Digital tools, including social media, content marketing, Search Engine Optimization (SEO), marketplaces, and e-commerce platforms, provide opportunities for MSMEs to sustain business performance during exchange rate fluctuations. This study is limited by its reliance on secondary data, making the findings conceptual rather than empirically validated. Nevertheless, it contributes to the literature on marketing management, entrepreneurship, and MSME development by positioning digital marketing as an adaptive capability that supports business resilience and informs sustainable digital transformation strategies.